Waqf reporting and governance of Johor and Federal Territory Islamic Religious Councils / Dalila Daud - Daud, Dalila (Institute of Graduate Studies, UiTM, 2018)
Waqf plays a critical role within the Islamic society. Indeed, it is a central feature in Islamic religious practices, socio-economy activities, poverty alleviation programs, charity, health, education as well as ways in curbing social problems. Despite its importance, there is a notable lack of proper waqf reporting among the Islamic Religious Councils who are responsible in waqf administration and control. As far as the waqf councils are concerned, there are serious questions regarding the quality and level of reporting conducted, which, in turn, reflects the ineffectiveness of the councils’ governance. Even though it is clear that the councils’ situation is dire, there have been few studies carried out to investigate this concern. The thesis therefore addresses this literature gap by providing insights on waqf reporting and governance of Islamic Religious Councils. In particular, this study aims to investigate the current practice and the governance practice in Islamic councils. These research issues are examined using a qualitative research methodology involving two Islamic councils in Malaysia…